Alcohol‐based deep eutectic solvent as a carrier of SiO2@Fe3O4 for the development of magnetic dispersive micro‐solid‐phase extraction method: Application for the preconcentration and determination of morin in apple and grape juices, diluted and acidic extract of dried onion and green tea infusion samples. Issue 17 (2nd July 2019) - Majidi, Seyedeh Maedeh; Hadjmohammadi, Mohammad Reza
Abstract: In this study, a hydrophilic deep eutectic solvent was synthesized as a carrier and disperser of magnetic nanoparticles based on ferrofluid and used to develop the dispersive micro‐solid‐phase extraction method. Ethylene glycol/tetramethylammonium chloride deep eutectic solvent and SiO2 @Fe3 O4 were used to provide the highly stable ferrofluid with strong sorbing properties without any additional stabilizer, which was employed to extract and determine morin in apple and grape juices, diluted and acidic extract of dried onion, and green tea infusion samples. The dispersibility of SiO2 @Fe3 O4 and prevention of its aggregation in the sample solution were improved using the deep eutectic solvent‐based ferrofluid. Also, it facilitated the fast injection of sorbent into the sample solution that led to an increase of the contact surface between the sorbent and analyte, and reduction of the extraction time and consumption of the sorbent. The important experimental parameters influencing the extraction efficiency of morin were examined. Under the optimal conditions, a linear calibration curve was obtained in the range of 3–500 µg/L with a determination coefficient of 0.9994. The limits of detection and quantification were of 0.91 and 2.98 µg/L, respectively. While an extraction recovery of 97.7% with relative standard deviation of 3.8% (interday) was obtained via three replicated measurements on a 30 µg/L of morin standard solution, the enrichment factor was 39.1. Finally, this method was successfully used to extract and preconcentrate morin in various samples, followed with their determination by high‐performance liquid chromatography with ultraviolet detection.